Vitamin K Antagonist Use and Risk for Intracranial Carotid Artery Calcification in Patients With Intracerebral Hemorrhage - Peeters, Michaël T. J.; Houben, Rik; Postma, Alida A.; van Oostenbrugge, Robert J.; Schurgers, Leon J.; Staals, Julie (Frontiers in Neurology, 2019)
Background Intracranial carotid artery calcification (ICAC) on Computed Tomography (CT) is a marker of atherosclerosis and an independent predictor of vascular events including stroke. While vitamin K antagonists (VKAs) are used to prevent embolic stroke, they have been shown to increase levels of both coronary and extra-coronary artery calcification. This has not been studied for (intracranial) carotid arteries. The aim of this study is to investigate the association between VKA use and degree of ICAC. We tested our hypothesis in a cohort of patients with non-traumatic intracerebral hemorrhage (ICH) of which a substantial part used VKAs. Materials and methods We retrospectively semi-quantified ICAC on brain unenhanced CT of consecutive adult patients with non-traumatic ICH. We used a 5-point visual scale and dichotomized degree of ICAC in low and high degree. Patient demographics, VKA use as well as known risk factors for intracranial calcification were collected. Univariable and multivariable logistic regression analysis was performed to investigate the association between ICAC and VKA use. Results 376 non-traumatic ICH patients were included of whom 77 were using VKAs (20.5%). Any degree of ICAC was detected in 289 patients (76.9%). Univariable analysis showed that a high degree of ICAC was significantly associated with older age (OR 1.06, 95% CI 1.03 – 1.08), hypertension (OR 2.14, 95% CI 1.27 – 3.62), diabetes mellitus (OR 2.38, 95% CI 1.27 – 4.49) and the use of VKAs (OR = 1.84, 95% CI 1.06 – 3.20). In multivariable regression analysis, only older age was significantly associated with a higher degree of ICAC (OR 1.05, 95% CI 1.02 – 1.08) while VKA use was not (OR 1.22, 95% CI 0.67 – 2.24). Conclusions Our findings do not support VKA use as an independent risk factor for higher ICAC degree. We could not confirm the concerns about VKA use and vascular calcification. We suggest further research in other cohorts with VKA users such as patients with ischemic stroke and atrial fibrillation and would recommend to include information on duration of VKA use.